Análisis del programa educativo Jclic para el aprendizaje de Química Inorgánica I con los estudiantes de tercer semestre de la carrera de Biología, Química y Laboratorio, período abril-julio 2017 - Pazos Pazos, Yolanda Nataly (2017)
The research work was based on the need to innovate and deal with technological tools, the problem being the lack of knowledge of programs involved in ICT as teaching resources for the development of learning. The objective was to analyze the Jclic educational program implemented for Inorganic Chemistry learning to the third semester of the Biology, Chemistry and Laboratory Career. It has as reference to the pedagogue David Ausubel with his theory of learning deals with the use of significant material as is the case of technological resources. This was achieved through a non-experimental, bibliographical and field research design, at an exploratory but descriptive level in a population of 23 students; the survey with its respective instrument the questionnaire was the implemented technique for the data collection. When analyzing the results it was determined that a high percentage of students favored the use of the educational programs in the moment of generating new knowledge, indicating clearly the support of the Tics to promote significant learning; it was concluded that the educational program Jclic is a didactic tool that contributes learning and facilitates the incorporation of new information in an orderly and natural way fulfilling the condition of being a potentially significant component, so that its use must be implemented since it has a great variety of new activities to motivate the student to pursue learning.